Avaliação do estado nutricional e consumo alimentar de crianças com alergia ao leite de vaca - Boaventura, Renata Magalhaes [UNIFESP] (2018)
Introduction: The Cow’s Milk Allergy (CMA) is frequent, mainly in children. The treatment is based on exclusion of milk and its products of diet, as the preparations with the food and orientation regarding substitute diet, which should meet the nutritional needs of each individual. Aim: to compare the anthropometric indices and food consumption of children with CMA and healthy controls. To evaluate serum vitamin A (retinol, betacarotene and lycopene) and 25 (OH) D levels of children with CMA and to relate them to variables associated with disease, food consumption, body composition and nutritional therapy. Methods: A crosssectional study with 57 participants, 27 from the CMA group and 30 controls. Z scores of body mass index (ZBMI) and height (ZH), cutaneous folds (tricipital and subscapular), food consumption (nonconsecutive 3day food record) and serum concentrations of retinol, betacarotene, lycopene, 25(OH)D, parathyroid hormone and ultrasensitive C reactive protein. Statistical analysis: Qui square, t Student, and MannWhitney test (P<0.05) Results: The predominant age in both groups was preschoolers, mean of 4 years (± 1.9). The CMA group had a ZH lower than the control [0.24 (2.1; 0.5) vs 0.19 (2.4; 1.9); p = 0.0043]. Regarding dietary intake, it was observed that the CMA group presented lower intakes of calcium (553.3 mg ± 260.3 vs 820.1 ± 328.8 mg, p = 0.0033) and lipds [24.7% (18.4, 37.5) vs 28.3% (19.2, 37.8); p = 0.0123]. Low serum concentrations of retinol, betacarotene, lycopene, 25 (OH) D was 25.9%, 59.3%, 48.1% and 74.1%, respectively. Children with CMA who receiving soy beverages and fruit juices presented lower serum concentrations of 25 (OH) D compared to the group receiving infant formulas or compounds (soy, extensively hydrolyzed and amino acids). Conclusion: Children with CMA consume smaller amounts of calcium and lipids and are lower than controls. Vitamin A and D insuficiency were frequently observed in CMA group, emphasizing the need for nutritional guidance and monitoring.